2015
DOI: 10.1016/j.wasman.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Waste generation rates and patterns: The case of Lebanon

Abstract: The objective of this study is to analyze Infectious Health Care Waste generation rates and patterns in Lebanon. Therefore, the quantities generated during five years by 57 hospitals from a total of 163 in the country have been analyzed. The seasonal evolution of Infectious Health Care Waste production and the evolution of the evaluation of the trends over years have been studied. Besides, the generation per capita have been estimated and compared to other countries. The variance between categories and the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
2
26
2
1
Order By: Relevance
“…To assess medical waste management during a crisis Analysing the policies, legislation, waste arisings, visits, interviews, and evaluation of treatment systems Production in hospitals was 683 kg a day, while the medical waste generation was, 3357 kg a day. Hazardous and non-hazardous waste was partially segregated, treatment of the medical waste was rarely done, 75% of hazardous waste was untreated A new methodology was proposed that could lead to better use of resources during a crisis Maamari et al (2015) Lebanon To analyse the generation rate of medical waste in Lebanon…”
Section: Gazamentioning
confidence: 99%
“…To assess medical waste management during a crisis Analysing the policies, legislation, waste arisings, visits, interviews, and evaluation of treatment systems Production in hospitals was 683 kg a day, while the medical waste generation was, 3357 kg a day. Hazardous and non-hazardous waste was partially segregated, treatment of the medical waste was rarely done, 75% of hazardous waste was untreated A new methodology was proposed that could lead to better use of resources during a crisis Maamari et al (2015) Lebanon To analyse the generation rate of medical waste in Lebanon…”
Section: Gazamentioning
confidence: 99%
“…For example, in Nanjing of China, researchers found that the medical waste generation rate ranges from 0.5 to 0.8 kg/bed day with a weighted average of 0.68 kg/bed/day [2]. In Lebanon, the obtained results showed that the average generation rate of large private hospitals was 2.45 kg per occupied bed per day [10]. In other study in China, the hospital medical waste generation rate was estimated based on diagnosis-related groups [11].…”
Section: Introductionmentioning
confidence: 99%
“…While there have been a number of previous studies evaluating factors such as waste generation rates, these have generally tended to focus solely on solid waste and on the environmental sustainability (e.g. Moreira and Gunter, 2013;Maamari et al, 2015;Caniato et al, 2015;Ren et al, 2016;He et al, 2016), with limited research on operational sustainability and the combined evaluation of solid and liquid wastes.…”
Section: Introductionmentioning
confidence: 99%